Strategi Pemenangan Kandidat Kepala Desa (Studi Kasus Kemenangan Polisi dalam Pemilihan Kepala Desa 2015 di Desa Kebasen Kecamatan Kebasen Kabupaten Banyumas) - Sulistiowati, Ratna (Universitas Negeri Semarang, 2018)
Village Head Election is made to choose as the village head of government leaders in the village. Similarly, the village head elections held in the village of Kebasen 2015 by one of the candidates was a cop. Therefore we need a winning strategy to bind the hearts of the people to win village elections. The purpose of this study is to determine the candidate winning strategy village chief of police in village elections in 2015 in the village of Kebasen and to find out how the village head candidate of the police in addressing weaknesses in the winning strategy in village elections in 2015 in the village of Kebasen. This study uses qualitative research and interviews conducted to prospective village chief of police, a successful team of candidates for village chief of police and the head of the election committee of the village. Results from this study that the strategy of winning are used by the prospective head of the village police along with the successful team that is first to form a successful team, then that determines the mass base of support, do ngendong, provide assistance to citizens in the form of materials or services that have been done long day and the campaign closed by giving gifts of money in lieu of money transport. While in overcoming weaknesses, successful team action for cadres who caught ambiguous by not given any real information about the strategy to be executed, and to avoid the negative things that happen on the road, the team successfully pick up the ball of citizens who live far to transfer to the polls. Advice given that the village government Kebasen better and experienced of the village chief to be able to keep kondusivitas Kebasen village and the next village election committee together with the Supervisory Committee to be more concerned about the conditions in order to prevent activities of political money.